2008
DOI: 10.1016/s1808-8694(15)30573-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of weight and height development in children after adenotonsillectomy

Abstract: The children that underwent adenotonsillectomy acquired a higher weight-height growth potential in relation to those children who were not operated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5] Adenotonsillar hypertrophy is the primary cause of OSAS in children, and is usually treated with adenotonsillectomy (AT). AT has been reported to accelerate weight [6][7][8][9][10][11][12][13][14] in children with baseline failure to thrive (FTT), 1,3,4,15 normal weight patients, 9,11,14,[16][17][18][19][20] obese individuals, 9,13,16,21,22 and infants. 10 The majority of studies also have demonstrated an increase in the height growth rate after AT for OSAS, 3,6,11,17,23,24 but other studies reported no significant differences.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…[1][2][3][4][5] Adenotonsillar hypertrophy is the primary cause of OSAS in children, and is usually treated with adenotonsillectomy (AT). AT has been reported to accelerate weight [6][7][8][9][10][11][12][13][14] in children with baseline failure to thrive (FTT), 1,3,4,15 normal weight patients, 9,11,14,[16][17][18][19][20] obese individuals, 9,13,16,21,22 and infants. 10 The majority of studies also have demonstrated an increase in the height growth rate after AT for OSAS, 3,6,11,17,23,24 but other studies reported no significant differences.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…Adenoidectomy is the standard treatment of obstructive adenoidal enlargement that is resistant to conservative treatment. It is a very common otolaryngological surgical procedure, and it has a variable outcome [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…13) A prospective study in 22 patients to evaluate the effect of adenotonsillectomy revealed that children that underwent adenotonsillectomy had more height and weight gain after 6 months later. 10) Recently, Katz, et al 11) conducted randomized controlled study to compare the effect on growth of adenotonsillectomy and watchful waiting in 464 children who had obstructive sleep apnea. Their results showed that adenotonsillectomy for children with sleep apnea results in significantly greater weight gain than watchful waiting 7 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies regarding the effects on growth pattern after childhood tonsillectomy, and some authors have reported that height and weight growth patterns normalized after tonsillectomy. [10][11][12][13] However, there are few studies on the long-term effects on growth or presenting symptoms. Furthermore, it is also unclear impact on growth according to preoperative growth status.…”
Section: Introductionmentioning
confidence: 99%